Structural racism through Sundown towns and its relationship to COVID-19 local risk and racial and ethnic diversity - Yulin Hswen; Franklin Yang; Circe Le-Compte; Margaret E. Hurley; Heather Mattie; Thu. T. Nguyen (Preventive Medicine Reports, 2023)
“Sundown towns” across the US prevented racial and ethnic minorities from living and working within their borders as they forced minorities to leave these towns after sunset. The objective of this study was to explore the relationship between sundown town status, COVID-19 local risk index and racial and ethnic diversity. A multi-level hierarchical model was used to examine the effect of historical segregation through sundown towns status on present day COVID-19 local risk index and city-level diversity. Over 2,400 Sundown towns were cataloged across the United States, with the greatest density in the Midwest. Sundown towns, which historically excluded racial and ethnic minorities, had significantly less city-level diversity and lower COVID-19 local risk index compared to non-Sundown towns. Findings show that Sundown towns perpetuate residual segregation which continues to impact current inequities in COVID-19 risk among racial and ethnic minorities at the neighborhood level. We recommend that public health officials for pandemic preparedness should devote greater resources to these historically segregated racial and ethnic minority areas because of the historic structural racism that has placed these places at higher risk.